Enforced Granulocyte/Macrophage Colony-stimulating Factor Signals Do Not Support Lymphopoiesis, but Instruct Lymphoid to Myelomonocytic Lineage Conversion - Iwasaki-Arai, Junko (The Rockefeller University Press, 2003)
We evaluated the effects of ectopic granulocyte/macrophage colony-stimulating factor (GM-CSF) signals on hematopoietic commitment and differentiation. Lineage-restricted progenitors purified from mice with the ubiquitous transgenic human GM-CSF receptor (hGM-CSFR) were used for the analysis. In cultures with hGM-CSF alone, hGM-CSFR–expressing (hGM-CSFR(+)) granulocyte/monocyte progenitors (GMPs) and megakaryocyte/erythrocyte progenitors (MEPs) exclusively gave rise to granulocyte/monocyte (GM) and megakaryocyte/erythroid (MegE) colonies, respectively, providing formal proof that GM-CSF signals support the GM and MegE lineage differentiation without affecting the physiological myeloid fate. hGM-CSFR transgenic mice were crossed with mice deficient in interleukin (IL)-7, an essential cytokine for T and B cell development. Administration of hGM-CSF in these mice could not restore T or B lymphopoiesis, indicating that enforced GM-CSF signals cannot substitute for IL-7 to promote lymphopoiesis. Strikingly, >50% hGM-CSFR(+) common lymphoid progenitors (CLPs) and >20% hGM-CSFR(+) pro-T cells gave rise to granulocyte, monocyte, and/or myeloid dendritic cells, but not MegE lineage cells in the presence of hGM-CSF. Injection of hGM-CSF into mice transplanted with hGM-CSFR(+) CLPs blocked their lymphoid differentiation, but induced development of GM cells in vivo. Thus, hGM-CSF transduces permissive signals for myeloerythroid differentiation, whereas it transmits potent instructive signals for the GM differentiation to CLPs and early T cell progenitors. These data suggest that a majority of CLPs and a fraction of pro-T cells possess plasticity for myelomonocytic differentiation that can be activated by ectopic GM-CSF signals, supporting the hypothesis that the down-regulation of GM-CSFR is a critical event in producing cells with a lymphoid-restricted lineage potential.